Peculiarities of CsPbBr3 perovskites melting in quasi-equilibrium conditions - Фочук, Петро Михайлович; Копач, Олег Вадимович; Копач, Василина Вікторівна; Bolotnikov, A.; James, Ralf (My University, 2024)
The melting behavior of CsPbBr3 perovskite was studied by differential thermal analysis (DTA). It was found that melting of CsPbBr3 occurs non-isothermally in the temperature range of 561-570 °C. From the temperature dependence of the solid-phase melting rate, it was established that at 567±1 °C the change in the mechanism of the solid-phase melting goes from fragmentation to dissolution at the surface. The obtained values of the activation energy of the melting of the solid phase in CsPbBr3 show that the activation energy of the dissolution of the solid-phase fragments is 4 times greater than the energy of the fragmentation of the solid phase.